ANALISIS PREFERENSI SISWA MELANJUTKAN KE SMK NEGERI 1 BANGKINANG KELOMPOK MULTIMEDIA T.P 2014/2015 - Mutia, Cut Mutia Cut; Asyari, Abu Asyari Abu (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract :This research aims to: a) analyza factors that become a preference for students who choose SMK 1 Bangkinang. b) analyze dominant factors that become a preference for students who choose SMKN 1 Bangkinang.Methot used in this research is descriptive research with total sampling technique. The results of this are a) factors that become a preference for students choose SMKN 1 Bangkinangis prioritied at a sector job. b) dominant factor that become a preference for student choose SMKN 1 Bangkinang is because of want to work stand alone 98,9% c) the category that become a preference a preference for students SMKN 1 Bangkinang for students SMKN 1 Bangkinang, globally show the preference students category choose SMK for hight category amount 55 persons (56%), medium category amount 21 persons (27%), and in low. Category amount 17 persons (17%), it means that preference for students choose SMK is high.   Keywords :Preference